Respuesta :

Just look at the x and y variables and their exponents and roots. Ignore the rest.

Start with x.
On the left side you have cubic root of x^c.
On the right side you have x^2.

[tex] \sqrt[3]{x^c} = x^2 [/tex]

[tex] (x^c)^{\frac{1}{3}} = x^2 [/tex]

[tex] \dfrac{c}{3} = 2 [/tex]

[tex] c = 6 [/tex]

Now look at y on both sides and the roots and exponents of y.

[tex] \sqrt[3]{y^5} = y\sqrt[3]{y^d} [/tex]

[tex] (y^5)^{\frac{1}{3}} = y^1 \times y^{\frac{d}{3}} [/tex]

[tex] y^{\frac{5}{3}} = y^{1 + \frac{d}{3}} [/tex]

[tex] y^{\frac{5}{3}} = y^{\frac{3}{3} + \frac{d}{3}} [/tex]

[tex] y^{\frac{5}{3}} = y^{\frac{d + 3}{3}} [/tex]

[tex] \dfrac{d + 3}{3} = \dfrac{5}{3} [/tex]

[tex] d + 3 = 5 [/tex]

[tex] d = 2 [/tex]

Answer: Choice C. c = 6; d = 2
ACCESS MORE